Sucinta análise sobre o novo crime de perseguição do Art. 147-A do Código Penal: stalking - Lai, Sauvei (2022)
Submitted by phemiran@stj.jus.br (phemiran@stj.jus.br) on 2022-01-14T19:18:19Z No. of bitstreams: 2 sucinta_analise_sobre_lai.pdf: 1024507 bytes, checksum: 998dec7f8042a761656896d5162c09fb (MD5) license.txt: 1239 bytes, checksum: c9b4c351324448672315a00808efb725 (MD5)